PENGARUH DESAIN INTERIOR DAN LOKASI BISNIS TERHADAP MINAT BELI KONSUMEN PADA WARUNG BAMBU KRUENG GEUEKUH - Fitri Ramadhan; Maisyura Maisyura (Negotium: Jurnal Ilmu Administrasi Bisnis, 2021)
This study aims to determine the effect of Interior Design and Business Location on Consumer Purchase Interest at Warung Bambu Krueng Geukuh. The research method in this study uses quantitative methods and information collected using a questionnaire. The population used in this study were visitors to Warung Bambu Krueng Geukuh. The sample used is the visitors to Warung Bambu Krueng Geukuh, totaling 60 people using the Accidental Sampling method. Test the validity of the data using Correland Item-Total Correlation r-Calculate and test the reliability using Alpha Cronbach. The analytical technique used is multiple regression analysis with hypothesis testing using the SPSS 25 program. The results of this study indicate that: (1) interior design has a positive effect on buying interest. (2) business location has a positive effect on buying interest. (3) interior design and business location have a positive effect on buying interest.